The China quarterly - University of London. Contemporary China Institute.; Congress for Cultural Freedom.; University of London. School of Oriental and African Studies. (Contemporary China Institute of the School of Oriental and African Studies, London University, 1960)
"An international journal for the study of China."In 1961 published by Congress for Cultural Freedom, Paris. In 1962-1967 published by Information Bulletin Ltd, London. From 1968 published by Contemporary China Institute of the School of Oriental and African Studies, London University.